2014
DOI: 10.1021/ol500266z
|View full text |Cite
|
Sign up to set email alerts
|

Caeruleanone A, a Rotenoid with a New Arrangement of the D-Ring from the Fruits of Millettia caerulea

Abstract: Caeruleanone A (1), a novel rotenoid with an unprecedented arrangement of the D-ring, was isolated with another two new analogues, caeruleanones B (2) and C (3), together with 11 known rotenoids from the fruits of Millettia caerulea. The structures of the new compounds were determined by spectroscopic data analysis, with that of 1 being confirmed by single-crystal X-ray diffraction. Compounds 2 and 3 displayed potent mitochondrial transmembrane potential inhibitory and quinone reductase induction activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Comparison of the 1 H NMR chemical shift values for H-5, H-6, H-3', and H-6' or other protons of 3 and (−)-2,3-dehydrorotenone showed that no obvious changes were observed for any protons other than H-6', and a similar observation was evidenced in other rotenoids (Fig. S12, Supporting Information) [15, 18, 19, 33, 36, 44, 45]. This indicates that an anisotropic effect from the C-4 carbonyl group is not a major contributor to the downfield signal for the 1 H NMR resonance for H-6' of trans -rotenoids.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Comparison of the 1 H NMR chemical shift values for H-5, H-6, H-3', and H-6' or other protons of 3 and (−)-2,3-dehydrorotenone showed that no obvious changes were observed for any protons other than H-6', and a similar observation was evidenced in other rotenoids (Fig. S12, Supporting Information) [15, 18, 19, 33, 36, 44, 45]. This indicates that an anisotropic effect from the C-4 carbonyl group is not a major contributor to the downfield signal for the 1 H NMR resonance for H-6' of trans -rotenoids.…”
Section: Resultssupporting
confidence: 55%
“…S12 (Supporting Information), the downfield signal observed for the 1 H NMR resonance for H-6' of trans -rotenoids is not influenced by the choice of solvents used, as supported by the data measured in the same or different deuterated solvents for several rotenoids and their epimers [15, 18, 19, 33, 36, 44, 45]. Comparison of the 1 H NMR chemical shift values for H-5, H-6, H-3', and H-6' or other protons of 3 and (−)-2,3-dehydrorotenone showed that no obvious changes were observed for any protons other than H-6', and a similar observation was evidenced in other rotenoids (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…For example, Millettia pachycarpa was used as an anthelminthic to evacuate the parasitic intestinal worms [7]. M. thonningii is known to treat dysentery, constipation, and diarrhea while M. carulea has anti-inflammatory effects [8,9]. M. macrophylla is also used to relieve menopausal symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…In an initial investigation of the fruits of this species, three new rotenoids including caeruleanone C ( 5 ), were isolated, along with 11 rotenoids of known structure. 42 Of these, caeruleanone C proved to be a potent inhibitor of mitochondrial transmembrane potential (MTP) (IC 50 0.07 μM). 42 The loss of MTP is regarded as an indication of apoptosis, and hence has been correlated with the anticancer potential of a given test compound.…”
Section: Selected Lead Bioactive Compounds Obtainedmentioning
confidence: 99%